Interdisciplinary Construction of a Socio-ecological Vulnerability Trajectory Based on the Quatre Montagnes (Isère, France) Area from 1950 to 2016 - Thomas Spiegelberger; Agnès Bergeret; Émilie Crouzat; Leita Tschanz; Delphine Piazza-Morel; Jean-Jacques Brun; Dominique Baud; Sandra Lavorel (Revue de Géographie Alpine)
The study of socio-ecosystems, their vulnerability, resilience and trajectories often requires collaboration between the human and social sciences, and the natural sciences. This article proposes to test this notion of socio-ecosystem and a methodology around the chronosystemic timeline as intermediate tools of interdisciplinary knowledge. It reports on an interdisciplinary experience, its research context, as well as its conceptual and methodological framework, illustrated with the example of the Quatre Montagnes in the Vercors Mountains (French Alps). It proposes a protocol that can be applied to monitoring the vulnerability trajectories of an association of municipalities and its environmental resources in an interdisciplinary perspective. The process consists of four stages: i) a sociohistorical and ecological exploratory step, ii) the determination of the dimensions to be observed and their indicators, iii) the construction of the timeline, and iv) the analysis of the vulnerability trajectory of a landscape including its actors. This article presents the potential, the methodological difficulties, and the critical issues of this interdisciplinary analysis.